MANAJEMEN DAKWAH DI TENGAH PERKEMBANGAN TEKNOLOGI INFORMASI - Suhadi Suhadi (Al-Din: Jurnal Dakwah dan Sosial Keagamaan, 2019)
Abstract The development of information technology enhances the management of missionary endeavor (da’wah) because the development of information technology is able to change the mindset and attitude patterns of mankind. In this process, the principles of missionary endeavor (da’wah) management must be applied by besides giving precise meaning about the meaning of communicator, media and audience that need to be developed on broader meaning through information technology. The use of information technology to support the management of missionary endeavor (da’wah) will provide effectiveness to the flow of missionary endeavor (da’wah).